Mechanical drawing - French, Thomas Ewing 1871-1944. (New York McGraw-Hill, 1974)
A textbook introducing the basic theory, techniques, and uses of drafting for industrial arts and vocational high school students.
First-7th editions by T. E. French and C. L. Svensen; 1st-3d editions published under title: Mechanical drawing for high schools.
Keywords: Mechanical drawing